2023
DOI: 10.1144/jgs2023-020
|View full text |Cite
|
Sign up to set email alerts
|

The 2023 Pazarcık (Kahramanmaraş, Türkiye) earthquake (M w 7.7): implications for surface rupture dynamics along the East Anatolian Fault Zone

Abstract: Southern Türkiye faced widespread catastrophic destruction by two devastating earthquakes on the same day. As the earthquakes occurred at 04:17 (Mw=7.7, Pazarcık, Kahramanmaraş) and 12:30 (Mw=7.6, Elbistan, Kahramanmaraş) on February 6, 2023, neighboring active fault systems were broken in succession between the Hatay and Malatya Provinces in the region. The first earthquake, one of the largest earthquakes in this region during the last century, caused widespread damage to infrastructure and buildings, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…1B). Slip at the surface is highly heterogeneous, which is consistent with field observations ( 18 ), but on average increases from the southwest to the northeast ends of the M w 7.8 rupture (fig. S8).…”
Section: The Geometrically Complex Mw 78-77 Earthquake Doubletsupporting
confidence: 89%
“…1B). Slip at the surface is highly heterogeneous, which is consistent with field observations ( 18 ), but on average increases from the southwest to the northeast ends of the M w 7.8 rupture (fig. S8).…”
Section: The Geometrically Complex Mw 78-77 Earthquake Doubletsupporting
confidence: 89%
“…The thin line connecting (C) and (D) points to the same blue data point. (E) Displacements along the EAFZ (excluding Narlı) plotted versus distance (+ is to northeast, – is to southwest) from fault intersection zone (table S1) ( 59 ). (F) Displacements from Sentinel-1 satellite data plotted along the length of the EAFZ ( 9 ).…”
Section: Seismological Background and Earthquake Characteristicsmentioning
confidence: 99%
“…The Mw 7.8 rupture initiated on the Narli fault, 15 km south of the main strand of the EAF (Fig. 3a) and later propagated bilaterally along the main strand of the EAF along the Erkenek segment towards the northeast and along the Pazarcik and Karasu/Amanos segments towards the southwest [6][7][8][9][10][11] . The second earthquake initiated on the Çardak fault (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3a). The 2023 doublet is the strongest earthquake documented on the EAFZ since 1114 CE 6,10 and represents a unique opportunity to map the active faults in the region. Indeed, several studies have suggested various segmentation models of the EAF that differ on the location of the active faults and active plate margins in this region 3,[12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%